2010
DOI: 10.1038/jhg.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Copy-number variations on the X chromosome in Japanese patients with mental retardation detected by array-based comparative genomic hybridization analysis

Abstract: Mental Retardation Consortium 8X-linked mental retardation (XLMR) is a common, clinically complex and genetically heterogeneous disease arising from many mutations along the X chromosome. Although research during the past decade has identified 490 XLMR genes, many more remain uncharacterized. In this study, copy-number variations (CNVs) were screened in individuals with MR from 144 families by array-based comparative genomic hybridization (aCGH) using a bacterial artificial chromosome-based X-tiling array. Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 44 publications
2
46
0
1
Order By: Relevance
“…It is noteworthy that congenital cataract and dental abnormalities were not pointed out in all the members (males and carrier females). 23 Thus, it is unlikely that the genomic rearrangement involving NHS causes congenital cataract and dental abnormalities as found in our family.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…It is noteworthy that congenital cataract and dental abnormalities were not pointed out in all the members (males and carrier females). 23 Thus, it is unlikely that the genomic rearrangement involving NHS causes congenital cataract and dental abnormalities as found in our family.…”
Section: Resultsmentioning
confidence: 70%
“…23 Most carrier females of IL1RAPL1 mutations and the carrier mother of the microduplication involving IL1RAPL1 showed normal intelligence. [23][24][25] In this study, one of the three affected females (MC18) had learning difficulties at school, which could be mild presentation of MR. As 18% of patients with BCOR mutations showed MR, 6 it is reasonable that the BCOR mutation, rather than IL1RAPL1 rearrangement, causes mild MR in MC18. Skewed and random X-inactivation in the mother (MC17b) and the elder daughter (MC17) was confirmed, respectively, in this family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…97,98 It was linked to nonsyndromic X-linked ID but also to general mental performance. [99][100][101][102][103][104][105] Most of the mutations described so far result in a loss-of-function of the protein, either by impairing the critical SAM-binding domain of the protein or by degradation of the mutant mRNA. 99,101 There are no morphological brain phenotypes in patients.…”
Section: Mitochondrial Phenotypesmentioning
confidence: 99%
“…They found novel copy-number aberrations and suggested that the results of X-tiling array are useful for the identification of cryptic copy-number aberrations containing novel genes responsible for diseases such as congenital disorders and X-linked MR. Recently, Honda et al 4 screened copy-number variations (CNVs) in individuals with MR from 144 families by array CGH using a bacterial artificial chromosome-based X-tiling array. They detected 10 (6.9%) pathogenic CNVs.…”
mentioning
confidence: 99%